2023
DOI: 10.1186/s13034-022-00536-0
|View full text |Cite
|
Sign up to set email alerts
|

Male-specific, replicable and functional roles of genetic variants and cerebral gray matter volumes in ADHD: a gene-wide association study across KTN1 and a region-wide functional validation across brain

Abstract: Attention deficit hyperactivity disorder (ADHD) is associated with reduction of cortical and subcortical gray matter volumes (GMVs). The kinectin 1 gene (KTN1) has recently been reported to significantly regulate GMVs and ADHD risk. In this study, we aimed to identify sex-specific, replicable risk KTN1 alleles for ADHD and to explore their regulatory effects on mRNA expression and cortical and subcortical GMVs. We examined a total of 1020 KTN1 SNPs in one discovery sample (ABCD cohort: 5573 males and 5082 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…The putamen is a dopamine-enriched structure involved in motor control and learning where volumetric differences have previously been associated with schizophrenia spectrum disorders and degenerative neuropsychiatric conditions. (95) For example, volumetric decreases in the left putamen and caudate are specifically associated with the presence of delusions in first episode schizophrenia (FEP). (96) The left putamen is also well-associated with cognitive (rather than motor) aspects of language processing, in particular phonological processing, articulation and language discrimination, including suggestive links to dopamine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The putamen is a dopamine-enriched structure involved in motor control and learning where volumetric differences have previously been associated with schizophrenia spectrum disorders and degenerative neuropsychiatric conditions. (95) For example, volumetric decreases in the left putamen and caudate are specifically associated with the presence of delusions in first episode schizophrenia (FEP). (96) The left putamen is also well-associated with cognitive (rather than motor) aspects of language processing, in particular phonological processing, articulation and language discrimination, including suggestive links to dopamine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…At present there are also studies showing either unaltered [58] (e.g. MDD) or increased volumes in special neuropsychiatric conditions characterized by dopaminergic activation, such as schizophrenia and autism and OCD [12].…”
Section: Discussionmentioning
confidence: 99%
“…There are also interesting neuropsychiatry studies revealing increased putaminal volumes in attention-deficit hyperactivity disorder (ADHD), pain, smoking, obsessive-compulsive disorder (OCD), neuroleptic exposure, autism, bipolar depression, and schizophrenia [12]. However, it is still unclear if comorbid conditions other than anxiety might affect the specific volumes in MDD, especially when it comes to unexpected volume alterations, such as increased putaminal and amygdala volumes.…”
Section: Introductionmentioning
confidence: 99%
“…The structure and volume of the PUT can be altered in various neurological and neuropsychiatric conditions [ 47 , 48 ], including PD [ 48 ], AD [ 49 , 50 ], amyotrophic lateral sclerosis (ALS) [ 51 , 52 ], obstructive sleep apnea (OSA) [ 53 , 54 ], and major depressive disorder (MDD) [ 55 ]. Parkinsonian Syndromes are notably associated with elevated iron concentration in the deep gray matter (DGM) nuclei [ [56] , [57] , [58] , [59] ].…”
Section: Introductionmentioning
confidence: 99%
“…Parkinsonian Syndromes are notably associated with elevated iron concentration in the deep gray matter (DGM) nuclei [ [56] , [57] , [58] , [59] ]. It has been suggested that the PUT is one of the primary regions affected by Parkinson's syndrome [ [60] , [61] , [62] , [63] ], which is age-dependent [ 48 , 59 , 64 ] and most prominently susceptible to the accumulation of iron [ 59 , 64 ]. Several studies, including meta-analyses, have also highlighted the significant accumulation of iron in the PUT of patients with Parkinsonism syndromes and PD, using postmortem and MRI measurements, including conventional MRI, SWI, and QSM techniques [ 57 , 65 ].…”
Section: Introductionmentioning
confidence: 99%